Foreign Direct Investment and Domestic Investment in Central, Eastern and South-Eastern Europe: A Multivariate Time Series Analysis - Bucevska, Vesna; Merdzan, Gunter (SCF Society and Bandirma Onyedi Eylol University, 2022)
The paper uses the autoregressive distributed lag (ARDL) approach to examine whether foreign direct investment (FDI) crowds in or crowds out domestic investment in the economies of Central, Eastern and South-eastern Europe from 1995-2021. The selected group of countries includes countries with different levels of economic development, countries from the former socialist system, countries that are in a transition process and countries that have successfully overcome that process. The breadth and diversity of the sample allow for obtaining statistically valid results. The results of the empirical research show that foreign direct investments have a shortterm crowding-out effect on domestic investments, followed by long-term crowding-in effects. Of course, this depends on the choice of control variables in the different models. However, it takes some time for such investments to affect the domestic economy fully. Furthermore, we found out that in some countries, institutions moderate the crowding-out effects of FDI. That is, institutional quality is found to be important in determining the relationship between domestic investment and FDI. JEL Classification: E22, F21, F41
Keywords: Domestic investment, Foreign direct investment, Economic growth, ARDL